2007
DOI: 10.1038/nprot.2007.241
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of maize

Abstract: Maize may be transformed very efficiently using Agrobacterium tumefaciens-mediated methods. The most critical factor in the transformation protocol is the co-cultivation of healthy immature embryos of the correct developmental stage with A. tumefaciens; the embryos should be collected only from vigorous plants grown in well-conditioned glasshouses. With the protocol described here, approximately 50% of immature embryos from the inbred line A188 and 15% from inbred lines A634, H99 and W117 will produce transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(141 citation statements)
references
References 37 publications
1
138
0
2
Order By: Relevance
“…This intensification in infection may have compromised embryo regeneration capability. Ishida et al (2007) showed that immature embryos expressing higher levels of the uidA reporter gene after the cocultivation stage were not the best ones to regenerate transgenic maize plants.…”
Section: Resultsmentioning
confidence: 99%
“…This intensification in infection may have compromised embryo regeneration capability. Ishida et al (2007) showed that immature embryos expressing higher levels of the uidA reporter gene after the cocultivation stage were not the best ones to regenerate transgenic maize plants.…”
Section: Resultsmentioning
confidence: 99%
“…Embryo axis was excised and the embryos were transferred to resting medium and incubated at 25 °C in the dark for 5 days. Some of the embryos after resting culture were examined histochemically for transient expression of GUS gene according to the procedure described by Ishida et al ( 2007 ). The embryos without used for GUS assay were placed on the fi rst selection medium that contained 5 mg/L of PPT or 15 mg/L of Hm and incubated for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This is a measure of transient genetic transformation. ISHIDA et al, (2007) recorded the positive effect of temperature shock when they achieved 52% transformation using physical stress, plus a temperature of 46 o C for 3min prior to infecting maize embryos. In like manner, pre-treatment at 43 o C (3min) prior to bacterial infection increased the sorghum transformation frequency from 2.6% to 7.6% (GUREL et al, 2009).…”
Section: Effect Of Temperature On the Infection Of Embryos With A Tumentioning
confidence: 99%
“…The Hi-II maize hybrid and its parents (A188 / B73) have been the most frequently used for genetic transformation (ISHIDA et al, 1996; FRAME Silva et al et al, 2011); however, these genotypes possess inferior agronomic characteristics (ISHIDA et al, 2007). Therefore, it becomes necessary to adapt the A. tumefaciens-mediated transformation parameters to agronomically suitable genotypes, like varieties, hybrids and lines (FRAME et al, 2006;WANG et al, 2007;CARNEIRO et al, 2009;GONZÁLEZ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%